Prevailing feeding and breeding management practices at commercial dairy farms in urban and peri-urban areas of Navsari district of Gujarat (Indian Journal of Animal Production and Management, 2024)
A field survey was carried out in Navsari district of South Gujarat to examine feeding and breeding  management practices adopted by commercial dairy farmers. For this purpose 20 dairy farms each in urban  and peri urban area were selected randomly. The required information was collected through personal  interview schedule. The observed data revealed that majority (92.5%) of the respondents had adopted  stall feeding and used to cultivate green fodder. Only 25% farmers were feeding concentrate to young  calves and 40% were feeding concentrate to heifers. Majority (80%) of the farmers was practicing chaffing  of green fodder and 82.5% used readymade concentrate feed. Only 20% farmers provided additional  concentrate to pregnant and lactating animals whereas, 75% followed special feeding after calving. Only  42.5% respondents were practicing mineral mixture feeding, among them 45% were urban and 40% were  peri urban farmers. The data was non significant among both regions. More than half the respondents  (55%) were breeding their animals by artificial insemination method,. Majority of the farmers were followed  pregnancy diagnosis (62.5%) and treatment of anoestrus /repeaters breeders but no respondents were  keeping breeding records.
Keywords: Breeding; Commercial dairy farm; Feeding; Management; Peri-urban; Practices; Urban areas